Concentration Properties of Extremal Parameters in Random Discrete Structures - Michael Drmota (Discrete Mathematics & Theoretical Computer Science, 2006)
The purpose of this survey is to present recent results concerning concentration properties of extremal parameters of random discrete structures. A main emphasis is placed on the height and maximum degree of several kinds of random trees. We also provide exponential tail estimates for the height distribution of scale-free trees.